Coastal responses to sea-level rise on centennial to millennial time scales: development of hybrid model-based forecasting for the Guadiana Estuary - Sampath, DMR (2016)
Tese de doutoramento, Ciências do Mar, da Terra e do Ambiente (Dinâmica Litoral), Faculdade de Ciências e Tecnologia, Universidade do Algarve, 2015